Wetting transition energy curves for a droplet on a square-post patterned surface - Gong, Wei; Zu, Yingqing; Chen, Sheng; Yan, Yuying (Elsevier, 2017)
Due to the property of water repellence, biomimetic superhydrophobic surfaces have been widely applied to green technologies, in turn inducing wider and deeper investigations on superhydrophobic surfaces. Theoretical, experimental and numerical studies on wetting transitions have been carried out by researchers, but the mechanism of wetting transitions between Cassie-Baxter state and Wenzel state, which is crucial to develop a stable superhydrophobic surface, is still not fully understood. In this paper, the free energy curves based on the transition processes are presented and discussed in detail. The existence of energy barriers with or without consideration of the gravity effect, and the irreversibility of wetting transition are discussed based on the presented energy curves. The energy curves show that different routes of the Cassie-to-Wenzel transition and the reverse transition are the main reason for the irreversibility. Numerical simulations are implemented via a phase field lattice Boltzmann method of large density ratio, and the simulation results show good consistency with the theoretical analysis.